Effects of Regional Government Financial Performance on Economic Growth, Unemployment, Poverty, and Human Development Index - susi astuti; mispiyanti mispiyanti (Universitas Tidar, 2020)
Good regional financial management can encourage economic growth in the area. A good quality of economic growth can improve the welfare of the community followed by a reduction in unemployment and poverty rates. This study aims to determine the effect of local government financial performance on economic growth, unemployment, poverty, and the Human Development Index. This study is to empirically prove that economic growth, unemployment, poverty, and the Human Development Index of districts in Central Java Province. The quality of economic growth affects the welfare of the community. Economic growth is usually followed by poverty reduction, an increase in the Human Development Index (HDI), and expansion of employment.The test tool used in this study was a simple regression analysis using the SPSS program. Data was obtained from the financial statements of the Regional Government and the Central Statistics Agency (BPS) to scientifically examine the effect of financial performance on economic growth, unemployment, poverty, and the Human Development Index. The results of this study indicate that independence, efficiency, effectiveness, operating expenditure, capital expenditure, growth, and dependence have no effect on the Human Development Index. While the degree of decentralization affects the Human Development Index. Independence, efficiency, effectiveness, dependency growth, and the degree of decentralization have no effect on poverty. Whereas operating expenditure and capital expenditure have an effect on poverty. Independence, effectiveness, capital expenditure, growth, dependency, and the degree of decentralization have no effect on unemployment. Whereas efficiency and operating expenditure affect unemployment. Independence, efficiency, effectiveness, operating expenditure, capital expenditure, growth, dependency, and the degree of decentralization have no effect on Economic Growth.